Plaguicidas en los agroecosistemas tropicales: evaluación del conocimiento actual del problema - Romero García, Alejandro (Revista de Biología Tropical, 1976)
Man is an integral part of the ecosystem and any action of his against the environment has an effect against man himself. An Agro-ecosystem is a unit composed of the total complex of organisms in an area under cultivation, plus the totality of the physical environmental conditions and the modifications introduced by man, who manages the agro-ecosystem for his own benefit. The use of pesticides has been necessary for the agricultural development of some tropical areas. Unfortunately, the inadequate use of this input has caused many problems for man himself. These include destruction of natural resources; intoxications; pesticide residues in water and foods; secondary pest outbreaks; increase in illnesses transmitted by certain arthropods; loss of foreign exchange; unemployment; malnutrition; disability; high infant mortality and poverty. A better use of agro-ecosystem management techniques can lead to a rational sustained utilization of land resources. Chemical pesticides can be considered as one of the factors in pest management, and not necessarily the only one available.